Utility of a multidisciplinary tumor board in the management of pancreatic and upper gastrointestinal diseases: an observational study. Issue 2 (February 2017) - Brauer, David G.; Strand, Matthew S.; Sanford, Dominic E.; Kushnir, Vladimir M.; Lim, Kian-Huat; Mullady, Daniel K.; Tan, Benjamin R.; Wang-Gillam, Andrea; Morton, Ashley E.; Ruzinova, Marianna B.; Parikh, Parag J.; Narra, Vamsi R.; et al.
Abstract: Background & objectives: Multidisciplinary tumor boards (MDTBs) are frequently employed in cancer centers but their value has been debated. We reviewed the decision-making process and resource utilization of our MDTB to assess its utility in the management of pancreatic and upper gastrointestinal tract conditions. Methods: A prospectively-collected database was reviewed over a 12-month period. The primary outcome was change in management plan as a result of case discussion. Secondary outcomes included resources required to hold MDTB, survival, and adherence to treatment guidelines. Results: Four hundred seventy cases were reviewed. MDTB resulted in a change in the proposed plan of management in 101 of 402 evaluable cases (25.1%). New plans favored obtaining additional diagnostic workup. No recorded variables were associated with a change in plan. For newly-diagnosed cases of pancreatic ductal adenocarcinoma (n = 33), survival time was not impacted by MDTB (p = .154) and adherence to National Comprehensive Cancer Network guidelines was 100%. The estimated cost of physician time per case reviewed was 190. Conclusions: Our MDTB influences treatment decisions in a sizeable number of cases with excellent adherence to national guidelines. However, this requires significant time expenditure and may not impact outcomes. Regular assessments of the effectiveness of MDTBs should be undertaken.